YouTubers vs. VTubers: Persuasiveness of human and virtual presenters in promotional videos - Sakuma, Hiroshi; Hori, Ao; Murashita, Minami; Kondo, Chisa; Hijikata, Yoshinori (Frontiers in Computer Science, 2023)
With the recent advances in motion tracking technologies and three-dimensional computer graphics software, communication through avatars has become increasingly popular. Can avatars be sufficiently persuasive, when compared to traditional forms of interpersonal communication? What factors contribute to the persuasiveness of virtual influencers? Existing literature has studied the differences in persuasiveness between human and virtual speakers extensively, particularly in education. However, few studies have been conducted on product promotion. Therefore, in this study, we investigated the characteristics of persuasiveness for humans and virtual influencers, as well as the differences between them in this regard in a more modern and practical situation: product introduction videos used in influencer marketing. Specifically, we recruited participants to watch product introduction videos on YouTube, presented by either humans or avatars. The videos were similar, except for the appearance of the presenter. Before and after watching the videos, the participants were asked to complete a questionnaire about their willingness to purchase the products and the characteristics of presenters' persuasiveness. The results show that although promotion via avatars can increase the participants' willingness to purchase, human influencers were more persuasive. However, the virtual YouTubers (VTubers) were more persuasive in certain product domains. VTubers who can change their appearance to match the product domain have potential for future applications. We also attempted to construct a model of persuasiveness in this pragmatic context based on Dyson's persuasiveness rating scale and the overall impression of the video. The degree of persuasiveness was found to be related to the presenters' likability, whether the presenter was a human or an avatar, the degree of familiarity between the presenter and the audience, the presenters' trustworthiness, and the quality as well as the entertainment level of the video. This model may be helpful for running successful promotions on YouTube. Our findings verify that avatars can be fairly persuasive in some situations, including promotional videos. These findings contribute to the future development of communication through avatars.